The Impact of Sudden Commencements on Ground Magnetic Field Variability: Immediate and Delayed Consequences. Issue 7 (8th July 2021) - Smith, Andrew W.; Forsyth, Colin; Rae, Jonathan; Rodger, Craig J.; Freeman, Mervyn P.
Abstract: We examine how Sudden Commencements (SCs) and Storm Sudden Commencements (SSCs) influence the occurrence of high rates of change of the magnetic field ( R ) as a function of geomagnetic latitude. These rapid, high amplitude variations in the ground‐level geomagnetic field pose a significant risk to ground infrastructure, such as power networks, as the drivers of geomagnetically induced currents. We find that rates of change of ∼30 nT min −1 at near‐equatorial stations are up to 700 times more likely in an SC than in any random interval. This factor decreases with geomagnetic latitude such that rates of change around 30 nT min −1 are only up to 10 times more likely by 65°. At equatorial latitudes we find that 25% of all R in excess of 50 nT min −1 occurs during SCs. This percentage also decreases with geomagnetic latitude, reaching ≤1% by 55°. However, the time period from the SC to 3 days afterward accounts for ≥90% of geomagnetic field fluctuations over 50 nT min −1, up to ∼60° latitude. Above 60°, other phenomena such as isolated substorms account for the majority of large R . Furthermore, the elevated rates of change observed during and after SCs are solely due to those classified as SSCs. These results show that SSCs are the predominant risk events for large R at mid and low latitudes, but that the risk from the SC itself decreases with latitude. Plain Language Summary: Rapid changes in the Earth's magnetic field can create the conditions for anomalous and potentially dangerous currents in spatially large networks such as power lines and pipelines. One phenomenon that can cause such rapid changes in the magnetic field are Sudden Commencements (SCs), driven by interplanetary shocks impacting the Earth's magnetosphere. In this work, we assess the risk due of SCs, finding that they contribute a significant fraction of large rates of change of the ground field at mid and low latitudes. SCs may also be followed by geomagnetic storms, and if we consider both the short SC intervals as well as a 3‐day period that follows we can account for the vast majority of large rates of change of the geomagnetic field, at mid and low latitudes. This work should help guide hazard estimates for energy providers, for example the time period after an SC in which they could expect large and potentially dangerous currents. Key Points: Sudden Commencements (SCs) are linked to 25% of rates of change above 50 nT min −1 at low geomagnetic latitudes, for example, <10° 90% of fluctuations above 50 nT min −1 occur within 3 days of an SC below 60° latitude Only Storm Sudden Commencements have a link with elevated rates of change of the field, either during the SSC or in the following days